A Study on the Marketing Strategies on the Performance of Banks: Impact of Marketing Strategies on Bank Performance in the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This paper examines the effect of marketingstrategies on banks performance in the Indian banking sector. Qualitative datawere sourced through the administration of structure questionnaire while thequantitative data were sourced from the various private and public banks. Thequantitative data were transformed to quantitative data with the use of Likertscale. The Ordinary Least Square estimation technique was employed foranalysis.